Design and Manufacture of Floating Hydroponic Planting Media Based on 3D Printing Technology - LAZUARDI, LAZUARDI; Zuhrohfi Immaroh, Nundiah; Hadi Susilo, Sugeng (Journal of Evrímata: Engineering and Physics, 2025)
This study examines the design and fabrication of innovative floating growing media based on 3D printing technology to support hydroponic systems in limited land and shallow waters. The design process was carried out using CAD software, then printed using a 3D printer with environmentally friendly PLA material. The four main components of the growing media produced were the Nutrition Tube, Nutrient Pipe, Buoy, and Water Grid, printed using constant parameters: a speed of 80 mm/min, a layer thickness of 0.2 mm, and a wall thickness of 0.8 mm. These parameters ensure precise dimensions and a sturdy structure. Tests showed that the growing media had stable buoyancy with a carrying capacity of up to 250 grams, buoyancy stability analysis used the CFD simulation method to determine the pressure distribution. The highest pressure was found in the Buoy area (12–15.89 Pa), while the bottom side of the float showed negative pressure (-4.9–0 Pa), indicating good hydrodynamic balance. These results indicate that 3D printing technology is effectively used in the development of lightweight, efficient, and customizable precision growing media, thus contributing to a sustainable floating farming system.